Level of awareness towards private retirement scheme : a case study on UiTM staff / Nur Adila Azman - Azman, Nur Adila (2019)
The Employees Provident Fund and pension scheme are the largest provident fund scheme available in Malaysia but currently there are not sufficient in funding the retiree. Thus, Private Retirement Scheme (PRS) was introduced in 2012 with the objective to improve living standards for Malaysians at retirement through addition savings funds.The main purpose of this exploratory study is to identify the level awareness of Private Retirement Scheme among UiTM staff and investigating any factors (knowledge, marketability and social) influencing the awareness towards Private Retirement Scheme among UiTM staff. This study applies quantitative approach with the use of survey questionnaires as the main instrument of data collection. A total of 100 respondents were selected for the purpose of this study. Data collected was analysed using descriptive analysis and Pearson Correlation Coefficient. In general, findings of this study show that relatively, the level of awareness towards Private Retirement Scheme is still low. In addition, only 40% of those that aware about this scheme. Various factors influencing awareness were found to have an influence on Private Retirement Scheme among UiTM staff. Overall, this study gives some information on the awareness towards Private Retirement Scheme among UiTM staff and factors influencing awareness on Private Retirement Scheme among UiTM staff.